Using tunability of ionic liquids to remove methylene blue from aqueous solution - Kermanioryani, M. (Elsevier Ltd, 2016)
The liquid-liquid extraction of Methylene Blue (MB) from aqueous solution was undertaken with 5 hydrophobic ionic liquids (ILs) based on bis(trifluoromethylsulfonyl)imide anion NTf2 for comparison purpose where three of them were of commercial origin, 1-butyl-3-methyl imidazolium BMIm, 1-hexyl-3-methylimidazolium HMIm and 1-octyl-3-methylimidazolium OMIm cations and the two other were purposely designed for this work, 1-hexyl-2-phenylimidazolium HPhIm, and 1-benzyl-3-methyl-imidazolium BnMIm. Several parameters such as the place and nature of the aromatic ring, the length of the side alkyl chain and the ability to form hydrogen bonding were investigated to evaluate their impact on extraction performances. Results show that the incorporation of the functional group (aromatic group) not only led to excellent results of dye removal compared to commercially available ones but allowed easier recovery and subsequent reuse of the functionalized ILs. Conductor like Screening Model for Real Solvents (COSMO-RS) calculations were also performed to see the structural variations of the ILs their extraction capabilities of MB from water. The finding of this study may assist in reducing the pollution of wastewater from dye industries. Â© 2016 Elsevier Ltd. All rights reserved.